Spectral Perspective on the Electromagnetic Activity of Cells - Kucera, Ondrej; Cervinkova, Katerina; Nerudova, Michaela; Cifra, Michal (Current Topics in Medicinal Chemistry, 2015)
In this mini-review, we summarize the current hypotheses, theories and experimental evidence concerning the electromagnetic activity of living cells. We systematically classify the bio-electromagnetic phenomena in terms of frequency and we assess their general acceptance in scientific community. We show that the electromagnetic activity of cells is well established in the low frequency range below 1 kHz and on optical wavelengths, while there is only limited evidence for bio-electromagnetic processes in radio- frequency and millimeter-wave ranges. This lack of generally accepted theory or trustful experimental results is the cause for controversy which accompanies this topic. We conclude our review with the discussion of the relevance of the electromagnetic activity of cells to human medicine.
Keywords: Radiofrequency